THE EXISTING PROFITABLE FINANCIAL MODEL OF MANAGEMENT - THE MAIN CAUSE OF THE CRISIS OF THE GLOBAL ECONOMIC SYSTEM AND THE COLLAPSE OF THE FINANCIAL SYSTEM - Myamlin, V. V. (Science and Transport Progress, 2008)
Inconsistencies of existing profit-financial model of the economy are exposed. The inoperability of such a model is demonstrated. A new field of economics (called as «megaeconomics»), aimed at study of the economy with other universal processes and phenomena, is suggested. The concept of non-profitable economy is proposed. General recommendations on overcoming a crisis in the country are given.